Impact of sampling time on the detection of mutations in rapidly proliferating tissues using transgenic rodent gene mutation models: A review. (15th November 2022) - Douglas, George R.; Beevers, Carol; Gollapudi, Bhaskar; Keig‐Shevlin, Zena; Kirkland, David; O'Brien, Jason M.; van Benthem, Jan; Yauk, Carole L.; Young, Robert R.; Marchetti, Francesco
Abstract: The OECD Test Guideline 488 (TG 488) for the Transgenic Rodent Gene Mutation Assay has undergone several revisions to update the recommended design for studying mutations in somatic tissues and male germ cells. The recently revised TG recommends a single sampling time of 28 days following 28 days of exposure (i.e., 28 + 28 days) for all tissues, irrespective of proliferation rates. An alternative design (i.e., 28 + 3 days) is appropriate when germ cell data is not required, nor considered. While the 28 + 28 days design is clearly preferable for slowly proliferating somatic tissues and germ cells, there is still uncertainty about the impact of extending the sampling time to 28 days for rapidly somatic tissues. Here, we searched the available literature for evidence supporting the applicability and utility of the 28 + 28 days design for rapidly proliferating tissues. A total of 79 tests were identified. When directly comparing results from both designs in the same study, there was no evidence that the 28 + 28 days regimen resulted in a qualitatively different outcome from the 28 + 3 days design. Studies with a diverse range of agents that employed only a 28 + 28 days protocol provide further evidence that this design is appropriate for rapidly proliferating tissues. Benchmark dose analyses demonstrate high quantitative concordance between the 28 + 3 and 28 + 28 days designs for rapidly proliferating tissues. Accordingly, our review confirms that the 28 + 28 days design is appropriate to assess mutagenicity in both slowly and rapidly proliferating somatic tissues, and germ cells, and provides further support for the recommended design in the recently adopted TG 488.